The distribution of match activities relative to the maximal intensities in elite soccer players: implications for practice - Riboli, A.; Esposito, F.; Coratella, G. (Research in Sports Medicine, 2022)
To determine the distribution of match-activities relative to maximum-intensities during official match in elite soccer players. One hundred and forty-eight Italian Serie A soccer players were monitored during 46 official matches (680 individual-samples). Total distance (TD), high-speed running (HSR), very high-speed running (VHSR), sprint, acceleration and deceleration were calculated. Maximum-intensities (1-minpeak) were used as the reference value to determine the distribution of relative intensity across the whole-match demands (90-minavg). Time and distance higher than 90-minavg (>90-minavg) were also calculated. The relative (m·min-1) 90-minavg vs1-minpeak was 59.6(4.4)% for TD, 26.2(4.4)% for HSR, 16.0(3.5)% for VHSR, 9.3(2.3)% for sprint, 19.2(4.6)% for acceleration and 15.4(5.2)% for deceleration. Total distance covered >90-minavg was ~61.4(5.0)% for TD, ~68.6(1.9)% for HSR, ~80.2(1.3)% for VHSR, ~95.7(0.4)% for sprint, ~75.5(1.3)% for acceleration and ~64.0(2.6)% for deceleration. With the exception of small [ES: 0.50 (0.26 to 0.73)] difference for acceleration, the relative distance >90-minavg was largely to very largely (ES: 1.64 to 7.78) higher (P<0.05) than the 90-minavg for each metric. While no between-position difference (P>0.05) was found for total minutes >90-minavg, between-position differences (P<0.05) for the total distance >90-minavg were retrieved across each metric. The distribution of the activities relative to maximal intensities could assist coaches for soccer training prescriptions.